2015
DOI: 10.1017/s0950268815001594
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of latent tuberculosis screening in HIV care centres: evaluation in a low tuberculosis incidence setting

Abstract: The screening and treatment of latent tuberculosis infection (LTBI) to prevent active tuberculosis (TB) is recommended by the WHO in all HIV-infected patients. The aim of this study was to evaluate its implementation within Belgium's HIV care. A multiple-choice questionnaire was sent to 55 physicians working in the country's AIDS reference centres. Response rate reached 62%. Only 20% screened all their HIV-infected patients for LTBI. Screening methods used and their interpretation vary from one physician to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…In the present study, it was found that LTBI screening among PLWH was performed significantly more frequently in foreignborn individuals coming from high TB incidence countries. This is in agreement with what has been observed in other European countries, such as the Netherlands (Evenblij et al, 2016), Belgium (Wyndham-Thomas et al, 2016), and Switzerland (Elzi et al, 2007), as well as in non-European countries, such as Australia (Doyle et al, 2014). In contrast, a study performed in the United States demonstrated an association between the request for screening for LTBI diagnosis and poverty (Reaves et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, it was found that LTBI screening among PLWH was performed significantly more frequently in foreignborn individuals coming from high TB incidence countries. This is in agreement with what has been observed in other European countries, such as the Netherlands (Evenblij et al, 2016), Belgium (Wyndham-Thomas et al, 2016), and Switzerland (Elzi et al, 2007), as well as in non-European countries, such as Australia (Doyle et al, 2014). In contrast, a study performed in the United States demonstrated an association between the request for screening for LTBI diagnosis and poverty (Reaves et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…In spite of the existing recommendations, there is evidence that even in resource-rich countries, a significant proportion of PLWH are not screened for LTBI diagnosis (WHO, 2019;Evenblij et al, 2016;Wyndham-Thomas et al, 2016). This may be due to the low accuracy of LTBI tests to predict the development of active TB (Diel et al, 2011;Petruccioli et al, 2016a;Goletti et al, 2018a;Goletti et al, 2018b), to the awareness of the reduction in TB risk in those on combined antiretroviral therapy (cART) (Girardi et al, 2004;Girardi et al, 2012), and to the lack of availability of LTBI tests in clinical centres (CDC, 2011;Web site, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A similar assessment of LTBI screening and treatment practices has been reported by Wyndham-Thomas et al [18]. The study was carried out in Belgium, which is, just as the Netherlands, a low-incidence country for tuberculosis, and showed similar findings.…”
Section: Discussionsupporting
confidence: 74%
“…Despite numerous guidelines, it has also been reported in several studies, that practices on the ground often differ substantially from what is recommended [ 39 41 ], and often a significant proportion of PLHIV do not receive screening for LTBI [ 37 , 40 , 42 ]. Uptake of LTBI screening in industrialized countries have ranged from 20% in Belgium, to 68.8% in US [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the possible reasons for non-adherence to recommendations on LTBI screening and treatment and pointed out to perceived low accuracy of LTBI tests or lack of sufficient evidence [ 37 , 40 ], perceived low risk for LTBI among PLHIV in the local settings or low risk among those on cART [ 39 ], fear of potential side effect and drug interactions and poor compliance [ 39 , 40 ]. One study even reported explicitly negative attitude towards guidelines, due to lack of end-user involvement in the development of such guidelines [ 39 ].…”
Section: Discussionmentioning
confidence: 99%